Pengaruh Informasi Akuntansi Terhadap Harga Saham Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia - Muhammad Anshor Panjaitan; Laylan Syafina (Owner : Riset dan Jurnal Akuntansi, 2023)
The presence of the capital market increases the choice of sources of funds for companies and increases investment choices which can be interpreted as opportunities to obtain additional funds for companies. In order for investors to want to invest, the company must provide information about financial statements. Stock trading on the stock exchange is related to accounting information related to company performance, this information is important for investors and business people. The technology sector is one of the stock sectors on the Indonesia Stock Exchange. The issue of digitalization among investors, which began in the industrial era 5.0, has made technology sector companies famous. The purpose of the study is to ascertain the partial and simultaneous effects of Earnings Per Share (EPS), Debt to Equity Ratio (DER), and Price Book Value (PBV) on stock prices in companies operating in the technology sector on the Indonesia Stock Exchange. This study is quantitative and makes use of secondary data from business financial reports. A total of 32 businesses from the technology sector that were listed on the Indonesia Stock Exchange throughout the 2019–2021 timeframe make up the research population. Purposive sampling was utilized for the sample, and numerous tests of linear regression were run on the data. The results of the study revealed that EPS had no substantial effect on stock prices. Stock prices are not much impacted by DER. Stock prices are positively and significantly impacted by PBV. The simultaneous impact of EPS, DER, and PBV on stock prices is substantial.